Translating stand-up comedy: Eddie Izzard's Dress to Circle - Whitworth, Kirsten (My University, 2009)
Abstract This research analyses the decisions made in the translation and performance, by Anglophone comedian Eddie Izzard, of a comedy show performed first in two parts in English, in Dress to Kill and Circle, and then translated by the performer and performed in French, as Dress to Circle. The study attempts to answer the questions surrounding the inclusion of certain material, and the resultant differences in the French and English versions, relying primarily on theories of relevance, contextualisation and equivalence. The major theories relied on for this research are frame semantics, relevance theory, and equivalence theories. The research takes the form of a case study of three particular texts and the relationships between them, adopting a descriptive rather than a prescriptive approach. Certain prescriptive categories (such as those expressed by Nida) are nonetheless used as descriptive labels for the kind of equivalence that does exist. The texts are analysed both as written texts and texts in performance, with attention paid to the delivery of the texts, and their reception. Given that the source and target texts are markedly different in terms of content, the texts are analysed in the light of their intention to provide humour and generate a positive response in the audience, taking into account the factors involved in live performance.